Guía didáctica para el desarrollo de la psicomotricidad gruesa y fina en los niños/as de primer año de educación básica en la Escuela “Lorenzo Licta” de la comunidad Pilapuchin, parroquia Chugchilan, cantón Sigchos, provincia de Cotopaxi, durante el año lectivo 2011-2012. - Pilaguano Pullopaxi, María Cristina (2015)
At the culmination of the development stage of learning more meaningful in the lives of human beings that is between four and six years should be implemented readiness, stage corresponding to first year of basic education. During this period must conduct activities to stimulate of gross and fine motor skills for children / as to achieve development that corresponds to this age. The theoretical basis of this project responds to a research process that allows us to define the development of gross and fine motor skills characteristics on cognitive, emotional, social, oral, written, graphic language and its integration into the basic functions of body lesquema, laterality, directionality, balance, coordination temporary space, space, rhythm, by means of what the child can act on its way to modify and modified .